Feedback control of thermo acoustic instabilities - Low, Raymond Shan Yin (Nanyang Technological University, 2020)
Thermoacoustic instabilities in a combustion process may be generated as a result of the coupling of an unsteady heat source and acoustic resonator. The “Rijke Tube” as a tool is greatly useful for studying the interactions and relations temperature, density and pressure variations of sound waves have on each other. P.L. Rijke discovered the “Rijke Tube” which is made up of a hollow open cylinder with a source of heat placed inside. The heat from the source is converted into sound through self-amplifying standing waves. The Rijke tube allows for the position of the heat source and the amount of heat input from the source to be varied to better understand the thermoacoustic phenomenon. The purpose of this study is to be able to observe and control the effect of adding a sound of a certain frequency to the Rijke tube while it is in operation to see if it has any effect on the thermo acoustic instabilities of the system using National Instrument’s analog discovery 2 with the integrated waveform software.